2015
DOI: 10.1007/s10661-015-4474-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial assessment of river surface water quality using multivariate statistical techniques: a study in Can Tho City, a Mekong Delta area, Vietnam

Abstract: The present study is an evaluation of temporal/spatial variations of surface water quality using multivariate statistical techniques, comprising cluster analysis (CA), principal component analysis (PCA), factor analysis (FA) and discriminant analysis (DA). Eleven water quality parameters were monitored at 38 different sites in Can Tho City, a Mekong Delta area of Vietnam from 2008 to 2012. Hierarchical cluster analysis grouped the 38 sampling sites into three clusters, representing mixed urban-rural areas, agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 15 publications
5
52
1
1
Order By: Relevance
“…The CA enabled us to categorize sampling locations based on water quality, so that in future studies, the number of sampling locations can be minimized for cost-effective monitoring of water quality in Tiaoxi River by choosing a few locations from each cluster based on the distance distribution and pollution levels in those locations. Previous studies have reported that a similar strategy has been successfully applied in water quality monitoring programs elsewhere [12,13,61,62], and the Tiaoxi River Taihu catchment is therefore similarly amenable to this rational approach. the number of sampling locations can be minimized for cost-effective monitoring of water quality in Tiaoxi River by choosing a few locations from each cluster based on the distance distribution and pollution levels in those locations.…”
Section: Cluster Analysis For Spatial Groupingmentioning
confidence: 99%
See 1 more Smart Citation
“…The CA enabled us to categorize sampling locations based on water quality, so that in future studies, the number of sampling locations can be minimized for cost-effective monitoring of water quality in Tiaoxi River by choosing a few locations from each cluster based on the distance distribution and pollution levels in those locations. Previous studies have reported that a similar strategy has been successfully applied in water quality monitoring programs elsewhere [12,13,61,62], and the Tiaoxi River Taihu catchment is therefore similarly amenable to this rational approach. the number of sampling locations can be minimized for cost-effective monitoring of water quality in Tiaoxi River by choosing a few locations from each cluster based on the distance distribution and pollution levels in those locations.…”
Section: Cluster Analysis For Spatial Groupingmentioning
confidence: 99%
“…the number of sampling locations can be minimized for cost-effective monitoring of water quality in Tiaoxi River by choosing a few locations from each cluster based on the distance distribution and pollution levels in those locations. Previous studies have reported that a similar strategy has been successfully applied in water quality monitoring programs elsewhere [12,13,61,62], and the Tiaoxi River Taihu catchment is therefore similarly amenable to this rational approach. …”
Section: Cluster Analysis For Spatial Groupingmentioning
confidence: 99%
“…The axes determined by PCA lie along the directions of maximum variance. PCA provides an objective way of calculating indices so that variation in the data can be accounted for as concisely as possible (Phung et al 2015). It provides information on the most meaningful parameters, which describes the whole data set interpretation, provides data reduction, and summarizes the statistical correlation among water quality constituents with minimum loss of the original information (Helena et al 2000).…”
Section: Principle Component Analysismentioning
confidence: 99%
“…Additionally, One-way Analysis of Variance (ANOVA) was used to consider the significance of the mean differences among groups of monitoring sites and seasonal factors. Spearman correlation analysis (SCA) was used to assess the relationships among dependent and independent variables (physicochemical parameters and WQI) [2,3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Namely, nine Physicochemical parameters, including DO, BOD 5 , COD, NH 4 + -N, PO 4 3--P; TSS, pH, temperature and total coliforms, were selected to calculate WQI. In the WQI, number ranges from 0 to 100, corresponding to different bands of colors, signifies better water quality when it is higher [2,5,7].…”
Section: Introductionmentioning
confidence: 99%